REGULATION OF WORKING MOBILITY AS A FACTOR OF REGION INVESTMENT ATTRACTIVENESS (ULYANOVSK REGION FOR EXAMPLE) - M. Rybkina; T. Rodionova; N. Laptev (Вестник университета)
In the article analyzed existing migration flows in Ulyanovsk region. Using cluster analysis recieved groups of region districts with same migration activities. Found out reasons that have influence on migration process. Analyzed influence of migration to labor market development and given recommends to reducing migration.